2021
DOI: 10.3390/w13020186
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Statistical Analysis of Water Quality and Trophic State in an Artificial Dam Reservoir

Abstract: Paldang Reservoir, located in the Han River basin in South Korea, is used for drinking water, fishing, irrigation, recreation, and hydroelectric power. Therefore, the water quality of the reservoir is of great importance. The main objectives of this study were to evaluate spatial and seasonal variations of surface water quality in the reservoir using multivariate statistical techniques (MSTs) along with the Trophic State Index (TSI) and Trophic State Index deviation (TSID). The empirical relationships among nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 58 publications
2
32
0
1
Order By: Relevance
“…As reported previously [7,68], TP appeared to be a better indicator of Chl-a than TN, the R 2 values of which were less than 0.1, except for the monsoon period of the drought years (Figure 6). Chl-a and TP showed a noticeable correlation in the post-monsoon periods of the normal and the flood groups, with R 2 values of 0.30 and 0.37, respectively.…”
Section: Empirical Regression Analysissupporting
confidence: 80%
“…As reported previously [7,68], TP appeared to be a better indicator of Chl-a than TN, the R 2 values of which were less than 0.1, except for the monsoon period of the drought years (Figure 6). Chl-a and TP showed a noticeable correlation in the post-monsoon periods of the normal and the flood groups, with R 2 values of 0.30 and 0.37, respectively.…”
Section: Empirical Regression Analysissupporting
confidence: 80%
“…Previous studies have reported that high COD levels are caused by high levels of non-biodegradable organic wastewater, increased inputs of several non-point source pollutants such as humic substances during rainfall, and internal production by algae and aquatic plants [29,42,76]. As with the Yeongsan River, the concentrations of COD are increasing in the Nakong, Han, and Geum Rivers, while BOD is declining [12,42,77]. The CHL-a concentration in the river has been growing, and more frequent algal blooms have occurred in recent years.…”
Section: Water Quality Monitoring and Water Quality Indexmentioning
confidence: 98%
“…The highest mean values of COD and BOD were found at sites S4 and S5, which receive wastewater discharge from two STPs. TP and TN are indicators of nutrient pollution [12]. As with BOD and COD, the highest mean TP and TN values were observed at sites S4 and S5, which receive wastewater discharge from the STPs serving Gwangju City.…”
Section: Identification Of Potential Pollution Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be shown how to reduce the imposing multi-index dataset to a single clustered nominal response. This is a new concept and it furnishes an alternative to extracting water quality classification information from small data [49][50][51][52][53][54][55][56]. This would quickly refashion the problem to the naiver non-linear saturated but 'unreplicated' form.…”
Section: Introductionmentioning
confidence: 99%